Lifestyles of higher education students: the influence of self- esteem and psychological well-being - Silva, Armando Manuel Marques (2016)
Background The transition to higher education can affect lifestyle-related factors. Objectives: To identify lifestyles of higher education students and analyse the influence of self-esteem and psychological well-being. Methods Correlational cross-sectional study. A total of 4,314 students partici- pated in the study. Online questionnaires were used: Estilo de Vida Fantástico (Fantastic Lifestyle Assessment) [1]; Questionário de Bem- estar Psicológico (Psychological General Well-Being Questionnaire) [2], and Escala de auto-estima de Rosenberg (Rosenberg Self-Esteem Scale [3]. Results Most students (85.3 %) have a healthy lifestyle. Lifestyle is strongly correlated with self-esteem and psychological well-being (p < 0.001). While analysing the association between self-esteem and psycho- logical well-being and the various lifestyle domains according to gen- der, a positive and significant correlation (p < 0.001) was found among female students, except for the Smoking domain (p = 0.393); in relation to psychological well-being, positive correlations were found in all domains. Among male students, positive and significant correlations (p < 0.001) were found in most lifestyle domains and self-esteem, except for the Smoking (p = 0.992), Alcohol and other drugs (p = 0.181) and Other behaviours (p = 0.442) domains; in rela- tion to psychological well-being, positive and significant correlations (p < 0.001) were found in most lifestyle domains, except for the Smoking (p = 0.458) and Other behaviours (p = 0.128) domains. Conclusions Based on the results, higher education institutions should support intervention projects to maintain high levels of psychological well- being and self-esteem, promoting healthy lifestyles.